Electrochemical and Adsorption Studies Of Gymnema Sylvestre Leaves Extract on Mild Steel in 1.0 N Hydrochloric Acid - Dr. P. Deivanayagam; J. Poopathi; J. Rajarajan; Dr. M Kathirvel; K.Arunkumar; N Marimuthu; T. A. Sunil raj; Dr. R Varadhaseshan; S Kumarasamy (International Journal of Scientific Research in Science and Technology, 2025)
In this article Gymnema sylvestre leaves extract have been taken for mild steel in 1.0N HCl was taken the adsorption studies and electrochemical studies were taken. The result approved in the conclusion area